Bortezomib in the Treatment of Multiple Myeloma - Ghobrial, Irene M.; Richardson, Paul G.; Anderson, Kenneth C.; SpringerLink (Online service) (Basel : Springer Basel : Imprint: Springer, 2011)
Multiple Myeloma (MM) is the second most common type of blood cancer, resulting from an overproduction of cancerous infection-fighting white blood cells, known as plasma cells. Plasma cells are a crucial part of the immune system responsible for the production of antibodies. Bortezomib is a promising anticancer drug targeting the proteasome. This proteasome inhibitor induces cell stress and apoptosis in the cancer cells. While multiple mechanisms are likely to be involved, proteasome inhibition may prevent the degradation of pro-apoptotic factors, permitting activation of programmed cell death in neoplastic cells dependent upon the suppression of proapoptotic pathways. This monograph on bortezomib is a valuable source of information for researchers and clinicians from the fields of oncology and pharmacology, working either in academia or the pharmaceutical industry.
Keywords: Medicine; Oncology; Toxicology; Cytology; Medicine & Public Health; Oncology; Cancer Research; Pharmacology/Toxicology.; Apoptosis